BRANDING AND DIGITAL MARKETING STRATEGIES TO INCREASE THE COMPETITIVENESS OF MADRASAH IBTIDAIYAH MUHAMMADIYAH WALIKUKUN IN THE ERA OF SOCIETY 5.0 - Surahman, Susilo (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The development of the Society 5.0 era requires educational institutions, including madrasas, to adapt to digital dynamics to increase competitiveness. This article aims to analyze branding and digital marketing strategies that can be applied by madrasas in facing challenges and opportunities in the current era. This study uses a qualitative approach with literature study methods and secondary data analysis. The results of the study show that strengthening branding through visual identity, superior values, and consistent narrative can build a positive image of madrasas. Meanwhile, the use of digital marketing such as educational content on social media, search engine optimization (SEO), and the consistency of data-driven "campaigns" can expand reach and interaction with the public. The combination of these two strategies not only increases the visibility of madrassas but also encourages stakeholder participation in creating a competitive education ecosystem. The implications of this research provide practical guidance for madrasah managers in designing effective communication strategies in the midst of digital transformation.